Systematic literature review on islamic bank customer adoption - Khamiliyah, Lili; Waspada, Ikaputera; Sari, Maya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The development of Islamic banking has been widespread in Muslim-majority and non-Muslim countries. In the process of such developments, it is known that the adoption of Islamic banking products and services is an interesting phenomenon to study. This study aims to uncover the supporting factors for adopting Islamic banking in various countries. With a systematic literature review approach to publications in databases of reputable journals, this study has recognized that the adoption process of Islamic banking can be understood through the Diffusion of Innovation theory, Theory of Planned Behaviour, and Theory of Reasoned Action, including modifications. The religiosity aspect is a factor that exerts internal influence in the adoption of Islamic banking, while the environmental support factor is an external factor that supports adoption. This study has confirmed that adoption theories have become a powerful platform for understanding the acceptance of religiously motivated products for consumers with different backgrounds of religiosity.